Tree Nuts Anaphylaxis in Preschool Age Children - Matias, J. (2020)
Summary: Introduction. The incidence of food-induced anaphylaxis (FIA) is increasing in young children. Although the commonest culprits are cow's milk and egg, FIA to tree nuts (TNs) have been increasing. Objective. Characterization of children referred to our allergy department due to TNs-induced anaphylaxis (TNs-FIA) during preschool age. Materials and methods. We have retrospectively included 25 children with clinical history of preschool TNs-FIA, proven by allergological work-up. TNs sensitization was assessed by skin prick tests and/or specific IgE. Results. The mean age of the first anaphylactic episode was 3.1±1.2 years. The majority (92%) had an allergic disease (52% asthma). The implicated TNs were cashew (11 children), walnut (8), pine nut (5), hazelnut (2) and almond (1). The reaction occurred after the first known ingestion in 68%. In 92%, symptoms appeared within 30 minutes after exposure. The most frequent clinical symptoms were mucocutaneous (96%), respiratory (80%) and gastrointestinal (52%). Twenty-one children were admitted to the emergency department, although only 48% were treated with epinephrine. An underneath IgE-mediated mechanism was proven in all cases. Immunologic cross-reactivity with other TNs was identified in 84%, and with peanut in 36%. Overall, in our center, TNs-FIA represents 18% of all causes of FIA. Conclusions. In preschool age children with TNs-FIA, cashew and walnut were the commonest implicated nuts. Most reactions occurred briefly after exposure to minimal amounts of TNs, demonstrating the high potency of these allergens. About one-third also had peanut sensitization. Potentially life-threatening TNs allergy can occur early in childhood and adequate management should be undertaken.